2008
DOI: 10.1523/jneurosci.4694-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Muscarinic Receptors in Rat Bladder Sensory Pathways Alters Reflex Bladder Activity

Abstract: Antimuscarinic drugs affect bladder sensory symptoms such as urgency and frequency, presumably by acting on muscarinic acetylcholine receptors (mAChRs) located in bladder sensory pathways including primary afferent nerves and urothelium. However, the expression and the function of these receptors are not well understood. This study investigated the role of mAChRs in bladder sensory pathways in vivo in urethane anesthetized rats. Intravesical administration of the mAChR agonist oxotremorine methiodide (OxoM) el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 52 publications
5
111
1
Order By: Relevance
“…Recently, it has been reported that the bladder urothelium secretes non-neurogenic acetylcholine, and that muscarinic receptors are expressed on bladder epithelial cells and on afferent nerve terminals in the bladder (3). The bladder urothelium also produces adenosine triphosphate (ATP) and the afferent nerve terminals in the bladder have purinergic receptors (14). In an animal experiment, ATP secreted by bladder epithelial cells influenced bladder activity, while a muscarinic receptor agonist evoked the release of ATP from cultured bladder epithelial cells (5).…”
mentioning
confidence: 99%
“…Recently, it has been reported that the bladder urothelium secretes non-neurogenic acetylcholine, and that muscarinic receptors are expressed on bladder epithelial cells and on afferent nerve terminals in the bladder (3). The bladder urothelium also produces adenosine triphosphate (ATP) and the afferent nerve terminals in the bladder have purinergic receptors (14). In an animal experiment, ATP secreted by bladder epithelial cells influenced bladder activity, while a muscarinic receptor agonist evoked the release of ATP from cultured bladder epithelial cells (5).…”
mentioning
confidence: 99%
“…23 It has been suggested that P2X receptors found on bladder sensory nerve terminals 24 may be activated by enhanced ATP release from the urothelium in pathologies such as SCI. 25 Kullmann et al 4 also reported that intravesical administration of Oxo-M induced bladder overactivity through the release of ATP from the urothelium in normal rats. Another possible mechanism is that Oxo-M directly activated mAChRs expressed on bladder afferent fibers since mAChRs are reportedly expressed on L6/S1 DRG cell bodies of bladder afferent neurons, suggesting that bladder afferent pathways might be under direct cholinergic control.…”
Section: Discussionmentioning
confidence: 97%
“…Figure 4 depicts possible interactions of urothelial cells with other bladder structures such as bladder nerves, interstitial cells, smooth muscle and blood vessels through autocrine (i.e., autoregulation) or paracrine mechanisms (release from nearby nerves or other cells). Examples of "sensor molecules" (i.e., receptors/ion channels) associated with neurons that have been identified in urothelium include receptors for bradykinin (110) neurotrophins (TrkA and p75) (453), purines (P2X and P2Y) (61, 86,111,379,628), norepinephrine (α and β) (53, 59, 357,383), acetylcholine (muscarinic and nicotinic) (43,46,108,355,356) protease activated receptors (PARs) (130,140), amiloride/mechanosensitive Na + channels (29,576,668), prostaglandin E 2 (PGE 2 ) receptors (EP1) (671), and a number of TRP channels (TRPV1, TRPV2, TRPV4, TRPM8, and TRPA1) (51,57,58,200,230,358,440,590,680) (Fig. 4).…”
Section: Neuron-like Properties Of the Urothelium: Interaction With Amentioning
confidence: 99%
“…Muscarinic receptors are expressed in the urothelium at high density (259) and there is a basal release of acetylcholine from the urothelium, which is increased by stretch and aging (694). Activation of the muscarinic receptors in the urothelium releases substances (e.g., ATP) that modulate afferent nerves and smooth muscle activity (50,148,259,355,356).…”
Section: Neuron-like Properties Of the Urothelium: Interaction With Amentioning
confidence: 99%